Flexor tendon repair with a polytetrafluoroethylene (PTFE) suture material - Polykandriotis, Elias; Besrour, Foued; Arkudas, Andreas; Ruppe, Florian; Zetzmann, Katharina; Bräuer, Lars; Horch, Raymund E. (Archives of Orthopaedic and Trauma Surgery, 2019)
BackgroundThere is a consensus that after a flexor tendon repair an aggressive rehabilitation protocol with early active motion can improve functional outcome, provided that the combination of material and suturing technique can meet the higher biomechanic demands. Bearing this in mind we evaluated a polytetrafluoroethylene (PTFE) suture (SERAMON((R)), Serag-Wiessner) as a possible material for flexor tendon repair.Materials and methods40 flexor tendons were harvested from fresh cadaveric upper extremities. 3-0 and 5-0 strands were used both in the polypropylene (PPL) as well as in the PTFE group. In the first phase of the study, we evaluated knotting properties and mechanical characteristics of the suture materials themselves. In the second phase, a 2-strand Kirchmayr-Kessler suture technique was applied for a core suture of a flexor tendon (n=16). In the third phase, we performed a tendon repair including an epitendinous running suture with 5-0 PPL or 5-0 PTFE material (n=22). One way ANOVA tests were performed.ResultsThe linear loading strength of single strand knotted PPL 3-0 was 19.870.59N. The linear loading strength of knotted PTFE 3-0 was 32.47 +/- 1.67N. For PPL 3-0 maximum linear strength was achieved with five knots, for PTFE 3-0 with eight knots. When a Kirchmayr-Kessler core-only repair was performed, then in the PPL group the loading strength of the repaired tendon was 30.74 +/- 9.77N. In the PTFE group the loading strength was 23.74 +/- 5.6N (p=0.10). However, all repairs in the PTFE group failed due to cheese wiring. When a Kirchmayr-Kessler core and epitendinous repair technique was used, then in the PPL group the loading strength of the repaired tendon was 49.90 +/- 16.05N. In the PTFE group the loading strength was 73.41 +/- 19.81N (p=0.006).Conclusion p id=Par4 PTFE demonstrates superior strength properties in comparison to PPL for flexor tendon repairs. However, standard 2 strand techniques have proved inadequate to bear the higher biomechanic demands.
CRIS-Team WoS Importer:2019-03-08